AI-Driven Biometric Feedback for Leadership Development: Enhancing Emotional Regulation in High-Stakes Environments - Zarah Choirotus Sadiyah; Eka Rohmah Maulidiya; Sintia Ariandini; Mochammad Isa Ansori (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
The development of Artificial Intelligence (AI) integrated with biometric technology has opened new opportunities in leadership development, particularly in enhancing emotional regulation capabilities within high-stakes environments. This study aims to analyze the role of AI-driven biometric feedback in improving self-awareness, emotional regulation, and decision-making quality among leaders. The study employs a systematic literature review approach by examining recent reputable scientific publications related to AI, biometrics, and leadership. The findings indicate that physiological data such as heart rate variability (HRV) and galvanic skin response (GSR), when processed through AI systems, can provide real-time feedback that enhances individuals’ ability to recognize and regulate emotions adaptively. Furthermore, the integration of this technology contributes to improved accuracy and consistency in decision-making under pressure. The results also reveal that the effectiveness of implementation is influenced by both technical and non-technical factors, including data quality, algorithm accuracy, and user acceptance. This study contributes to strengthening the integration of psychological and technological approaches in modern leadership research and offers practical implications for developing data-driven leadership training programs in the digital era.